665 Gender differences of heart rate variability in patients with ischemic stroke (Balneo and PRM Research Journal, 2024)
(1) Background: Heart rate variability (HRV) is a parameter useful in monitoring post stroke cardiac dysautonomia. Our study is aimed at investigating HRV modifications in patients with stroke; (2) Methods: We investigated HRV parameters in 35 men and 35 women with stroke, data compared to 70 age and sex similar healthy subjects. We collected and interpreted HRV data related to resting state, deep breathing, and standing situations; (3) Results: The variables identified by classification methods to be discriminative in stroke groups for men and women classes are VLFms2, LFms2, LFnu, HFnu, and ApEn in resting state conditions, mean RR, HR, pNN50, VLFms2, LFnu, HFnu, ApEn and SampEn in deep breathing conditions, and mean RR, HR, HFnu, ApEn, and DFAa1 in standing conditions; (4) Conclusions: Monitoring of HRV in patients who have suffered an ischemic stroke is essential, as it is known that stoke contributes to an increased risk of cardiac autonomic dysfunction and consequently to a second unwanted vascular event.